Wychowanie dziecka w polskiej kulturze w warunkach emigracji na przykładzie polskich szkół sobotnich w Londynie - Zamecka-Zalas, Olga (Kultura-Społeczeństwo-Edukacja, 2021)
The aim of the article is to present the problem of raising a child in emigration, in Polish culture and national tradition, on the example of Polish Saturday schools in London. To implement the research problem, a monographic method was used, as well as a critique of documents and previous literature in this field. The result of the research is to present the role and merits of Polish schools of native subjects in the upbringing of children in emigration, based on the example of institutions operating in London. The article presents various forms of cooperation between Saturday schools and parents in the process of national education of their children. The patriotic upbringing of several generations of young Poles who are aware of their roots and are proud of their origins, is a great merit of the Polish schools of native subjects in London.